The Bombycoidea and Mimallonoidea (Lepidoptera) of a research station in the grasslands of Southern Brazil - Carvalho, Ana Paula S.; Laurent, Ryan A. St; Romanowski, Helena P. (Zootaxa, 2021)
We report the Bombycoidea and Mimallonoidea (Lepidoptera) observed at the the Universidade Federal do Rio Grande do Sul’s (UFRGS) Agronomic Research Station in Eldorado do Sul, Rio Grande do Sul, Brazil from September 7th to November 6th, 2018. This research station is situated in the Campos Sulinos (southern Brazilian grasslands) environment. As part of our inventory, we report the following Bombycoidea: 29 species of Sphingidae, 26 species of Saturniidae, at least seven species of Apatelodidae, and at least four species of Bombycidae. Within Mimallonidae we recorded eight species. New state records include the following Sphingidae: Xylophanes alineae, X. crenulata, and Perigonia stulta; and Mimallonidae: Mimallo grisea and the genus Menevia. Our study represents the first inventory of moths from this location and one of the few from the Campos Sulinos more broadly.